1978
DOI: 10.1161/01.cir.57.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Active valvulitis associated with chronic rheumatic valvular disease and active myocarditis.

Abstract: From ten patients aged 15 to 40 years with chronic rheumatic valvular disease and histologically proved Aschoff bodies of active rheumatic myocarditis, the valves were evaluated for incidence, distribution and degree of severity of active inflammation. Prior to death, there had been clinical evidence of active rheumatic fever. In each case, active rheumatic valvulitis was present in at least one valve. Of the individual valves studied, 83% were involved by active inflammation of the leaflets or the anulus or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…1 Since 1924, a number of studies have demonstrated the histopathology of this disease with correlations of the degree of rheumatic activity, which include the presence of Aschoff bodies, nonspecific edema, and leukocyte infiltration. 2,3 Despite the high prevalence, increased morbidity, and well-described histopathological findings of this disease, little is known about the cellular mechanisms responsible for calcification in these valves. Recently, our laboratory and others have demonstrated that calcification in nonrheumatic, "degenerative" stenotic aortic valves removed at the time of surgical valve replacement is associated with an osteoblast-like phenotype.…”
mentioning
confidence: 99%
“…1 Since 1924, a number of studies have demonstrated the histopathology of this disease with correlations of the degree of rheumatic activity, which include the presence of Aschoff bodies, nonspecific edema, and leukocyte infiltration. 2,3 Despite the high prevalence, increased morbidity, and well-described histopathological findings of this disease, little is known about the cellular mechanisms responsible for calcification in these valves. Recently, our laboratory and others have demonstrated that calcification in nonrheumatic, "degenerative" stenotic aortic valves removed at the time of surgical valve replacement is associated with an osteoblast-like phenotype.…”
mentioning
confidence: 99%
“…These data are similar to those described by several authors. 14,28,29 Some patients presented with rupture of chordae tendineae in the first rheumatic fever attack. These findings were previously reported, and chordae tendineae rupture is explained by the inflammatory reaction, Aschoff nodules consisting of central fibrinoid degeneration, and Anitschkow cells.…”
Section: Discussionmentioning
confidence: 99%
“…The carditis of ARF is a pancarditis, with valvulitis being the most common presentation [63]. It ranges widely in severity from mild sub-clinical involvement (16.8%) [64] to severe carditis with congestive heart failure and/or death (20%) [56].…”
Section: Current Epidemiology Of Gas Arf and Rhd Around The Worldmentioning
confidence: 99%